PLANNING AND PRODUCTION CONTROL THROUGH THE TAKT TIME CONCEPT: takt time - Ricardo Generoso da Silva, Celso; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2025)
Takt Time is a fundamental tool in production management, used to synchronize the activities of a production line with market demand. This study presents a comprehensive literature review on Takt Time, exploring its concept, calculation methods, application in different industrial sectors, and impact on production operations. Through the analysis of case studies and relevant research, best practices and challenges associated with Takt Time implementation are identified, providing valuable insights for companies interested in optimizing their operational efficiency. The results indicate that Takt Time can be a powerful tool to maximize productivity, reduce waste, and improve product quality when implemented properly and integrated with other production management practices.